Meningkatkan Hasil Belajar Shooting Bola Basket melalui Metode Pembelajaran Teaching at the Right Level (TaRL) pada Siswa Kelas X-3 SMAN 3 Jombang Tahun pelajaran 2022-2023 - Aulia Rahman (Departement of Mathematics Education, 2023)
Education aims to prepare future generations of the nation who have three main competencies, namely character, critical thinking, being able to solve problems by increasing literacy and numeracy skills. School as a formal institution in the education system is inseparable from efforts to improve students' learning achievement. Research objectives The purpose of this research is